Abscisic acid modulates differential physiological and biochemical responses to cadmium stress in Brassica napus. Issue 1 (31st December 2023) - Liao, Yiqun; Tang, Ying; Wang, Shiwei; Su, Huiling; Chen, Jing; Zhang, Dawei; Wu, Jinfeng; Zhou, Dinggang; Yan, Mingli; Liu, Lili
ABSTRACT: The plant hormone abscisic acid (ABA) has been proved to be a key protector against abiotic stresses at appropriate concentrations. This study aimed to investigate the role of ABA in alleviating cadmium (Cd) stress in two Brassica napus of oil-vegetable dual-purpose (Youfei 1 and Xiangyou 787). Cd stress disturbed the normal growth of rapeseed, however, specific ABA concentrations could alleviate the effects of Cd stress in B. napus. The results confirmed that exogenous ABA mitigates the negative effects of Cd-induced plant toxicity in B. napus by increasing growth traits, enhancing pigment molecules, enhancing gas exchange in leaves, as well as regulating antioxidation and the expression levels of genes related to Cd stress. This study indicated that ABA played an important protective role in regulating cadmium resistance in Brassica napus, and provided basic data for its application in actual production.